Pengaruh Kualitas Layanan dan Fomo terhadap Minat Penggunaan Bank Digital di Indonesia dengan Kepercayaan sebagai Variabel Moderasi - Pandawa, Rengga Yoga (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study aims to analyze the effect of service quality and Fear of Missing Out (FOMO) on public interest in using digital banks in Indonesia, with trust as a moderating variable. With the increasing digitalization in the banking sector, understanding the factors that drive public interest in digital banking has become crucial, particularly amid concerns over service security and reliability. This study employs a quantitative approach with a survey method involving 464 respondents, both users and non-users of digital banking services across Indonesia. Data analysis was conducted using the Partial Least Square - Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS software version 4.1.0.2. Service quality was measured using indicators such as reliability, accessibility, responsiveness, and service personalization. Meanwhile, FOMO was measured through indicators such as the perception of missing out, social anxiety, drive to adopt new technology, and social media influence. The results show that service quality has no significant effect on digital banking interest. However, FOMO has a significant positive effect on public interest in using these services. Additionally, trust has a significant but negative moderating effect on the relationship between FOMO and usage interest. This means that as trust in digital banking increases, the influence of FOMO on interest tends to decrease. This suggests that users who already trust the security of digital banking make more rational decisions and are less influenced by trends or social pressure. On the other hand, trust does not moderate the relationship between service quality and digital banking interest.